A Rare and Spectacular Rhododendron from Kameng District - Sahni, K. C.; Naithani, H. B. (Indian Forester, 1979)
Rhododendron dalhowsiae Hook f. var. rhabdotum (Balf f&Cooper) Cullen, a very rare, spectacular and endemic shrub is recorded for the first time from Arunachal Pradesh. It was first collected in 1915 bY Cooper from Bhutan and again by Sberrif also from Bhutan in 1934 Balfour described Cooper’s collection as R. rhabdatum Balf f et Cooper. Cullen and Ghamberlain have recently treated this species as a variety of R. dulhlhouiae Hook. F. and call it R dalhousiue var. rhabdotum (Balf. f. et Cooper) Cullen. This taxon is fucing the hazards of extincion in Arunchal and Bhutan owing to the massive road building and develop-mental activities there. To save this Rhododendron from extincnion it. removal from the wild should be hanned and its culture in recognized Government Botanical Gardens in the Eastern Himalaya is recommended.